2021
DOI: 10.4149/km_2021_2_79
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatments on microstructure and mechanical properties of Al0.5CoCrFeNi complex concentrated alloy

Abstract: The effect of heat treatments on microstructure and mechanical properties of Al0.5CoCr FeNi complex concentrated alloy (CCA) was studied. The CCA was prepared by vacuum induction melting of pure elements and solidification in ceramic crucibles. The as-solidified alloy was subjected to heat treatments consisting of solid solution annealing, water quenching and precipitation hardening. The microstructure of the as-solidified alloy consists of fcc(A1) dendrites and an interdendritic region composed of bcc(B2), bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…6d shows the formation of elongated particles oriented nearly perpendicularly to the load axis in the BCC(B2)/BCC(A2) region. The same particles were found in the BCC(B2)/BCC(A2) region in ascast Al 0.5 CoCrFeNi alloy and identified to belong to the FCC(A1) phase [32]. More intense precipitation of ductile FCC(A1) particles in BCC(B2)/BCC(A2) region and inhomogeneous precipitation of BCC(B2) in FCC(A1) dendrite matrix occur during tensile deformation at 900 • C. Formation of needle-like BCC(B2) precipitates due to high-temperature tensile loading within FCC(A1) matrix with composition given in Table 1 was observed recently by Lapin et al [47] in DS Al 0.5 CoCr 1.3 FeNi 1.3 (Ti, Si, B, C) 0.3 alloy.…”
Section: Numerical Simulation Of Tensile and Compression Testssupporting
confidence: 59%
“…6d shows the formation of elongated particles oriented nearly perpendicularly to the load axis in the BCC(B2)/BCC(A2) region. The same particles were found in the BCC(B2)/BCC(A2) region in ascast Al 0.5 CoCrFeNi alloy and identified to belong to the FCC(A1) phase [32]. More intense precipitation of ductile FCC(A1) particles in BCC(B2)/BCC(A2) region and inhomogeneous precipitation of BCC(B2) in FCC(A1) dendrite matrix occur during tensile deformation at 900 • C. Formation of needle-like BCC(B2) precipitates due to high-temperature tensile loading within FCC(A1) matrix with composition given in Table 1 was observed recently by Lapin et al [47] in DS Al 0.5 CoCr 1.3 FeNi 1.3 (Ti, Si, B, C) 0.3 alloy.…”
Section: Numerical Simulation Of Tensile and Compression Testssupporting
confidence: 59%
“…The CCAs are also compositionally complex alloys but the rules concerning the number of elements and coexisting phases, concentration range, and magnitude or importance of configurational entropy satisfy not only to HEA definition but also include many other alloys including concentrated ternary and quaternary alloys. It has been reported that CCAs based on quaternary Co-Cr-Fe-Ni can serve as a good base for the design of CCAs strengthened by intermetallic and ceramic phases for high-temperature structural applications [12]. He et al [13] have reported outstanding tensile properties of the alloy with nominal composition (FeCoNiCr)94Ti2Al4 (at.%), which has been achieved by precipitation of nanosized L12-Ni3(Ti, Al) particles in CoCrFeNi HEA matrix.…”
Section: Introductionmentioning
confidence: 99%